2019
DOI: 10.1002/jcp.29115
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Silencing of tumor‐suppressive NR_023387 in renal cell carcinoma via promoter hypermethylation and HNF4A deficiency

Abstract: Dysregulation of the epigenetic status of long noncoding RNAs (lncRNAs) has been linked to diverse human diseases including human cancers. However, the landscape of the whole-genome methylation profile of lncRNAs and the precise roles of these lncRNAs remain elusive in renal cell carcinoma (RCC). We first examined lncRNA expression profiles in RCC tissues and corresponding adjacent normal tissues (NTs) to identify the lncRNA signature of RCC, then lncRNA Promoter Microarray was performed to depict the whole-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Corroborating finding are identified in a previous study, which demonstrated that HNF4A is involved in the pathogenesis of endometriosis 9 . Moreover, it was reported in a prior research that HNF4A deficiency diminished renal cell carcinoma cell proliferation, migration and invasion 18 . Moreover, HNF4A upregulation could trigger inhibition of hepatocellular carcinoma proliferation 19 .…”
Section: Discussionsupporting
confidence: 55%
“…Corroborating finding are identified in a previous study, which demonstrated that HNF4A is involved in the pathogenesis of endometriosis 9 . Moreover, it was reported in a prior research that HNF4A deficiency diminished renal cell carcinoma cell proliferation, migration and invasion 18 . Moreover, HNF4A upregulation could trigger inhibition of hepatocellular carcinoma proliferation 19 .…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, the samples used in these studies (19). Based on the lncRNA Promoter Microarray and combined analysis of the lncRNAs expression profiles, Zhou et al identified a series of down-regulated lncRNAs with hypermethylated promoter regions (24). To our best knowledge, few systemic studies have focused on the lncRNAs in plasma of ccRCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, several studies had focused on the expression profile of lncRNA in ccRCC tissues (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Many lncRNAs are confirmed to be involved in the pathogenesis of ccRCC (19,21,23,24). Nevertheless, few studies have evaluated the roles of plasma lncRNAs in the diagnosis of ccRCC.…”
Section: Backgroundsmentioning
confidence: 99%
“…Cyclin D1 was also demonstrated to directly bind to HNF4α and cause a decrease in downstream genes expression (61). Previous studies in renal cell carcinoma reported that decreased HNF4α expression is positively correlated with e-cadherin expression, suggesting a poor prognosis in patients (62)(63)(64). Furthermore, HNF4α expression is blocked by mutated IDH, which could promote biliary cancer progression (65).…”
Section: Regulatory Roles Of Hnf4α In Human Cancersmentioning
confidence: 99%